One-step preparation and application of dopamine polymer with near-infrared region II light absorption capability
Through a one -step legal dopamine polymer, the problem of limited effects of the existing near -infrared light absorption materials in optical therapy has been solved, and the dual function of light thermal and optical power of the material has been achieved, which significantly improves its light absorption in the near -infrared region. Ability and antibacterial effect.
Patent Information
- Application Number
- CN202411462232.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-18
AI Technical Summary
In optical therapy applications, existing near-infrared light absorbing materials face problems such as few materials, complex preparation process, high cost, limited production on a large scale, and difficulty in controlling dual functions of photothermal and photodynamics, resulting in limited effect in clinical applications. .
Through a one-step preparation method, a dopamine polymer with near-infrared II region light absorption ability was prepared. The material showed strong light absorption characteristics in both near-infrared I and II region bands and had dual functions of photothermal and photodynamic forces. , can effectively kill bacteria.
The material has a simple preparation method, has diversified operations, can effectively absorb light above 1500nm, significantly improves the material's photothermal and photodynamic antibacterial effects, enhances bactericidal efficiency, and broadens its application scope in the treatment of diseases in vivo.
Smart Images

Figure CN119331247A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedicine technology, and specifically relates to a one-step preparation method of a dopamine polymer having near-infrared II region light absorption capability and its photothermal / photodynamic antibacterial application. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Bacterial infections seriously threaten human health. Antibiotic resistance is gradually becoming a global public health crisis. Bacterial resistance seriously weakens the therapeutic effect of traditional antibiotics. The development of new antibacterial strategies has become a major problem that needs to be solved urgently in the global biomedical field. As an emerging non-invasive treatment method, phototherapy, especially photothermal and photodynamic therapy, has attracted much attention because of its unique treatment mechanism that can effectively avoid bacterial resistance.
[0004] The photothermal conversion effect and photochemical reaction caused by near-infrared light (NIR, 780-1700nm) can effectively kill pathogens without damaging normal tissues. At the same time, it can penetrate the skin and other tissues well and penetrate deep into the lesion site. Therefore, it has great application potential in the treatment of diseases in vivo. Among them, NIR II light (1000-1700nm) has greater application advantages due to its higher biosafety and deeper tissue penetration depth. However, existing NIR light absorbing materials still face some challenges in realizing phototherapy applications. First, there are few materials that can efficiently absorb NIR band light; second, the preparation process of these materials usually involves complex chemical synthesis steps, which not only increases the production cost, but also limits its large-scale production and application; in addition, the effect of single therapy in phototherapy is often limited. Materials with dual functions of photothermal and photodynamic can better exert the therapeutic effect, but at present, there are great difficulties in the regulation of dual functions of photothermal and photodynamic. There are few single materials that can have both photothermal and photodynamic functions, and different materials are often required to be used in combination.
[0005] There is currently a lack of multifunctional materials on the market that can simultaneously meet the above requirements, which not only limits the further development of phototherapy technology, but also affects its wide clinical application. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a one-step preparation method of a dopamine polymer with near-infrared II light absorption ability and its photothermal / photodynamic antibacterial application. The material exhibits strong light absorption characteristics in both near-infrared I and II bands through a simple synthesis method, has both photothermal and photodynamic dual functions, and can effectively kill bacteria.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The first aspect of the present invention provides a one-step preparation method of a dopamine polymer having near infrared II region light absorption capability, comprising:
[0009] dissolving cobalt salt and 2-methylimidazole in an organic solvent to obtain a mixed solution containing cobalt salt and 2-methylimidazole;
[0010] Dopamine hydrochloride is added to the mixed solution containing the cobalt salt and 2-methylimidazole, and the mixture is reacted under preset conditions to obtain a dopamine polymer.
[0011] In some embodiments, the cobalt salt is cobalt nitrate.
[0012] In some embodiments, the molar ratio of the cobalt salt to 2-methylimidazole is 1:50-60, or 1:55.
[0013] In some embodiments, the molar ratio of the cobalt salt to dopamine hydrochloride is 1:0.15 to 1:150, or 1:1.5.
[0014] In some embodiments, the organic solvent is an ethanol aqueous solution.
[0015] In some embodiments, the volume ratio of ethanol to water is 2:1 to 2:5, or 2:3.
[0016] In some embodiments, the preset condition is stirring at room temperature, hydrothermal reaction or ultrasonic reaction.
[0017] In some embodiments, the stirring time at room temperature is 3 to 5 hours, or 4 hours.
[0018] In some embodiments, the hydrothermal reaction is carried out at 110-130° C. for 2-6 h, or at 120° C. for 4 h;
[0019] In some embodiments, the ultrasonic treatment is performed for 20-60 min, or 40 min.
[0020] More specifically, they include:
[0021] Dissolving cobalt nitrate in an ethanol aqueous solution containing 2-methylimidazole, adding dopamine hydrochloride thereto, and reacting for a period of time by stirring at room temperature, hydrothermal or ultrasonic methods, and obtaining a dopamine polymer after the reaction is completed;
[0022] The second aspect of the present invention provides a dopamine polymer having near-infrared II region light absorption capability prepared by the above method.
[0023] The third aspect of the present invention provides the use of the above-mentioned dopamine polymer in the preparation of photothermal / photodynamic antibacterial materials or devices.
[0024] Beneficial Effects of the Invention
[0025] (1) The present invention prepares dopamine polymer materials by a one-step method, the preparation method is simple, the process is simplified, and the experimental steps are reduced; at the same time, the preparation means are diversified and the operation is easier to implement.
[0026] (2) The dopamine polymer material prepared by the present invention covers the ultraviolet-visible-near infrared region in terms of light absorption range and can effectively absorb light with a wavelength of more than 1500nm. This improvement improves the material's ability to effectively utilize light, especially enabling it to exhibit excellent performance in the near-infrared II region, effectively broadening the application range of the material.
[0027] (3) The dopamine polymer material prepared by the present invention has the dual functions of photothermal and photodynamic under laser irradiation, so that it can generate local high temperature through photothermal effect and produce reactive oxygen species (ROS) through photodynamic effect to resist bacteria during the light response process. This dual-functional property can significantly enhance the application effect of the material in sterilization and greatly improve the sterilization efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0029] Figure 1 The UV-visible-near-infrared absorption spectra of the nanomaterials prepared in Examples 1 to 12 of the present invention; wherein a is the UV-visible-near-infrared absorption spectra of the solid samples obtained in Examples 1 to 4, b is the UV-visible-near-infrared absorption spectra of the solid samples obtained in Examples 5 to 8; c is the UV-visible-near-infrared absorption spectra of the solid samples obtained in Examples 9 to 12; d is the UV-visible-near-infrared absorption spectra of Examples 1 to 4 dispersed in water by ultrasound;
[0030] Figure 2 X-ray diffraction (XRD) patterns of the nanomaterials prepared in Examples 1 to 4 of the present invention;
[0031] Figure 3 The Fourier transform infrared (FTIR) spectra of the nanomaterials prepared in Examples 1 to 4 of the present invention;
[0032] Figure 4 is the full X-ray photoelectron spectroscopy (XPS) spectrum of Example 1 of the present invention;
[0033] Figure 5 are scanning electron microscope (SEM) images of the nanomaterials prepared in Examples 1 to 4 of the present invention; wherein a is the SEM image of Example 1, b is the SEM image of Example 2, c is the SEM image of Example 3, and d is the SEM image of Example 4;
[0034] Figure 6 are transmission electron microscope (TEM) images of the nanomaterials prepared in Examples 1 to 4 of the present invention; wherein a is the TEM image of Example 1, b is the TEM image of Example 2, c is the TEM image of Example 3, and d is the TEM image of Example 4;
[0035] Figure 7 The nanomaterials prepared in Examples 1 to 4 of the present invention are subjected to NIR light of different wavelengths (1.0 W / cm 2 ) Temperature variation diagram under irradiation for 10 minutes; wherein, a is the temperature variation diagram under irradiation with 808nm NIRⅠ light, and b is the temperature variation diagram under 1064nm NIRⅡ light;
[0036] Figure 8 The nanomaterials prepared in Examples 1 to 4 of the present invention were dispersed in water (concentration of 1 mg / mL) after ultrasonic treatment and then illuminated under NIRⅠ light (808 nm, 1.0 W / cm 2 ) is irradiated for 10 minutes and heated to the highest temperature; wherein a is the infrared thermal imaging image of the material obtained in Example 1, b is the infrared thermal imaging image of the material obtained in Example 2, c is the infrared thermal imaging image of the material obtained in Example 3, and d is the infrared thermal imaging image of the material obtained in Example 4;
[0037] Fig. 9 The fluorescence emission spectra of the nanomaterials prepared in Examples 1 to 4 of the present invention after being dispersed in aqueous solution and adding the active oxygen probe DCFH-DA; wherein a is the fluorescence emission spectra of Example 1 under NIRⅠ light (808nm, 1.0W / cm 2 ) after irradiation for 0 and 5 min, b is the fluorescence emission spectra of Example 2 under NIRⅠ light (808 nm, 1.0 W / cm 2 ) after irradiation for 0 and 5 min, c is the fluorescence emission spectra of Example 3 under NIRⅠ light (808 nm, 1.0 W / cm 2) after irradiation for 0 and 5 min, d is the fluorescence emission spectra of Example 4 under NIRⅠ light (808 nm, 1.0 W / cm 2 ) Fluorescence emission spectra after irradiation for 0 and 5 min;
[0038] Fig.10 This is a diagram showing the effect of the nanomaterial prepared in Example 1 of the present invention on anti-Escherichia coli after being irradiated with 808nm laser in NIRⅠ region;
[0039] Fig.11 This is a diagram showing the effect of the nanomaterial prepared in Example 1 of the present invention on anti-Staphylococcus aureus after being irradiated with a 1064nm laser in the NIR II region;
[0040] Fig.12 Schematic diagram of the preparation of the material of the present invention and its photothermal / photodynamic antibacterial effect. DETAILED DESCRIPTION
[0041] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0042] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0043] Example 1
[0044] A one-step preparation method of a dopamine polymer having near-infrared II region light absorption capability comprises the following steps:
[0045] (1) 29.2 mg of cobalt nitrate hexahydrate, 454.0 mg of 2-methylimidazole and 292.0 mg of dopamine hydrochloride were dissolved in an ethanol aqueous solution containing 4 mL of ethanol and 6 mL of deionized water, and stirred at room temperature for 4 h. The product was collected by centrifugation, washed with ethanol three times, and dried in a drying oven at 60° C. for 12 h to obtain a dopamine polymer material. The molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride was 1:1.5.
[0046] Example 2
[0047] The difference from Example 1 is that the molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride in step (1) is adjusted to 1:0.15, that is, in step (1), 29.2 mg of cobalt nitrate hexahydrate and 2.9 mg of dopamine hydrochloride are added.
[0048] Example 3
[0049] The difference from Example 1 is that the molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride in step (1) is adjusted to 1:15, that is, in step (1), 29.2 mg of cobalt nitrate hexahydrate and 29.2 mg of dopamine hydrochloride are added.
[0050] Example 4
[0051] The difference from Example 1 is that the molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride in step (1) is adjusted to 1:150, that is, in step (1), 29.2 mg of cobalt nitrate hexahydrate and 584.0 mg of dopamine hydrochloride are added.
[0052] Example 5
[0053] (1) 29.2 mg of cobalt nitrate hexahydrate, 454.0 mg of 2-methylimidazole and 2.9 mg of dopamine hydrochloride were dissolved in an ethanol aqueous solution containing 4 mL of ethanol and 6 mL of deionized water to obtain a mixed solution, which was placed in a 25 mL high pressure sealed reactor for hydrothermal reaction at 120° C. for 4 h. After the reaction was completed, the mixture was cooled naturally, and the obtained sample was centrifuged to collect the product, which was then washed with ethanol for 3 times and dried in a drying oven at 60° C. for 12 h to obtain a dopamine polymer material. The molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride was 1:0.15.
[0054] Example 6
[0055] The difference from Example 5 is that the molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride in step (1) is adjusted to 1:1.5, that is, in step (1), 29.2 mg of cobalt nitrate hexahydrate and 29.2 mg of dopamine hydrochloride are added.
[0056] Example 7
[0057] The difference from Example 5 is that the molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride in step (1) is adjusted to 1:15, that is, in step (1), 29.2 mg of cobalt nitrate hexahydrate and 292.0 mg of dopamine hydrochloride are added.
[0058] Example 8
[0059] The difference from Example 5 is that the molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride in step (1) is adjusted to 1:150, that is, in step (1), 29.2 mg of cobalt nitrate hexahydrate and 584.0 mg of dopamine hydrochloride are added.
[0060] Example 9
[0061] (1) 29.2 mg of cobalt nitrate hexahydrate, 454.0 mg of 2-methylimidazole and 2.9 mg of dopamine hydrochloride were dissolved in an ethanol aqueous solution containing 4 mL of ethanol and 6 mL of deionized water to obtain a mixed solution, and the mixed solution was ultrasonically treated for 40 min. After the reaction was completed, the obtained sample was centrifuged to collect the product, and then washed with ethanol for 3 times, and dried in a drying oven at 60° C. for 12 h to obtain a dopamine polymer material. The molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride was 1:0.15.
[0062] Example 10
[0063] The difference from Example 9 is that the molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride in step (1) is adjusted to 1:1.5, that is, in step (1), 29.2 mg of cobalt nitrate hexahydrate and 29.2 mg of dopamine hydrochloride are added.
[0064] Embodiment 11
[0065] The difference from Example 9 is that the molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride in step (1) is adjusted to 1:15, that is, in step (1), 29.2 mg of cobalt nitrate hexahydrate and 292.0 mg of dopamine hydrochloride are added.
[0066] Example 12
[0067] The difference from Example 9 is that the molar ratio of cobalt nitrate hexahydrate to dopamine hydrochloride in step (1) is adjusted to 1:150, that is, in step (1), 29.2 mg of cobalt nitrate hexahydrate and 584.0 mg of dopamine hydrochloride are added.
[0068] The light absorption properties of the nanomaterials prepared in Examples 1 to 12 of the present invention were tested:
[0069] Figure 1 The ultraviolet-visible-near-infrared absorption spectra of the nanomaterials prepared in Examples 1 to 12 of the present invention; wherein, a is the ultraviolet-visible-near-infrared absorption spectra of the solid samples obtained in Examples 1 to 4, b is the ultraviolet-visible-near-infrared absorption spectra of the solid samples obtained in Examples 5 to 8; c is the ultraviolet-visible-near-infrared absorption spectra of the solid samples obtained in Examples 9 to 12; d is the ultraviolet-visible-near-infrared absorption spectra of Examples 1 to 4 dispersed in water by ultrasound; all 12 samples have strong light absorption capabilities in the ultraviolet-visible-near-infrared region, wherein the light absorption region of the samples can reach above 1500nm, indicating that they have the basis for optical applications in the near-infrared II region;
[0070] The nanomaterials prepared in Examples 1 to 4 of the present invention were characterized in terms of material structure and morphology:
[0071] in, Figure 2The XRD patterns of the nanomaterials prepared in Examples 1 to 4 of the present invention are as follows: Figure 2 It can be seen that when the dopamine hydrochloride content is the lowest, Example 2 shows obvious characteristic peaks of the metal organic framework material ZIF-67, and as the dopamine hydrochloride content further increases, the diffraction peak intensity of Example 1 is weakened compared with Example 2, and the crystallinity decreases. When the dopamine hydrochloride content continues to increase, Example 4 eventually transforms into an amorphous structure;
[0072] Figure 3 The FTIR images of the nanomaterials prepared in Examples 1 to 4 of the present invention are as follows: Figure 3 It can be seen that the materials prepared in the four embodiments have a -1 、1510cm -1 and 1600cm -1 Obvious characteristic absorption peaks appear at 3100~3687cm, corresponding to phenol CO group, amino group and benzene ring group. -1 The broad absorption bands in the range are attributed to the stretching vibrations of NH and OH bonds. These characteristic peaks indicate the presence of polydopamine; the material prepared in Example 2 has a peak at 756 cm -1 The peak at 995-1301cm is the absorption peak of Co-N bond stretching vibration. -1 The range is the bending vibration absorption peak of the imidazole ring and the out-of-plane bending vibration absorption, 1301~1508cm -1 The absorption peak in the range is the stretching vibration of the imidazole ring, 1574 cm -1 The peaks at are the absorption peaks of the C=N bond in the imidazole ring, which are the characteristic peaks of ZIF-67. At this time, the content of dopamine hydrochloride is the lowest. With the increase of dopamine hydrochloride content, the characteristic peaks of ZIF-67 gradually disappear while the characteristic peaks of dopamine polymer become more obvious. This result shows that the microstructure of the material can be effectively controlled by controlling the ratio of reactants.
[0073] Figure 4 is the full XPS spectrum of Example 1 of the present invention; Figure 4 As can be seen in the figure, the full spectrum shows four characteristic peaks of Co 2p, C 1s, N 1s and O1s, which also proves the successful preparation of dopamine polymer;
[0074] Figure 5 are SEM images of the nanomaterials prepared in Examples 1 to 4 of the present invention; wherein a is the SEM image of Example 1, b is the SEM image of Example 2, c is the SEM image of Example 3, and d is the SEM image of Example 4; Figure 5 It can be seen from a that the material in Example 1 is an amorphous cluster structure formed by the aggregation of nanoparticles, and the structure is clear; Figure 5In b, it can be seen that the surface of Example 2 is relatively rough, and some of it has the structural characteristics of ZIF-67, and the particle size is relatively uniform; as the amount of dopamine hydrochloride added increases, the surface of the nanoparticles becomes smoother and smoother, showing obvious morphological changes, such as Figure 5 As shown in c and d, the surface of the material becomes smooth and round, and the coating layer becomes obviously thicker, resulting in an increase in particle size and a gradual regularization of particle shape;
[0075] Figure 6 TEM images of the nanomaterials prepared in Examples 1 to 4 of the present invention, wherein a is the TEM image of Example 1, b is the TEM image of Example 2, c is the TEM image of Example 3, and d is the TEM image of Example 4; Figure 6 In a, it can be seen that Example 1 shows clusters of nanoparticles. As the content of dopamine hydrochloride increases, the particles gradually increase in size, the morphology becomes more regular, and the surface becomes smoother. In Example 2 with the lowest content of dopamine hydrochloride, part of the particles present a hexagonal structure, indicating the presence of ZIF-67. As the content of dopamine hydrochloride increases, the morphology gradually evolves into a more regular spherical elliptical shape, that is, the polymer characteristics become more obvious, such as Figure 6 As shown in Example 4 in d;
[0076] The photothermal and photodynamic properties of the nanomaterials prepared in Examples 1 to 4 of the present invention were tested:
[0077] Photothermal properties test
[0078] Figure 7 The nanomaterials prepared in Examples 1 to 4 of the present invention are subjected to NIR light of different wavelengths (1.0 W / cm 2 ) for 10 minutes; wherein a is a temperature change diagram of 808 nm NIRⅠ light irradiation, and b is a temperature change diagram of 1064 nm NIRⅡ light irradiation; Figure 7 It can be seen that the temperature increases significantly with the increase of irradiation time;
[0079] Figure 8 The nanomaterials prepared in Examples 1 to 4 of the present invention were dispersed in water (concentration of 1 mg / mL) after ultrasonic treatment and then illuminated under NIRⅠ light (808 nm, 1.0 W / cm 2 ) is irradiated for 10 minutes and heated to the highest temperature; wherein a is the infrared thermal imaging image of the material obtained in Example 1, b is the infrared thermal imaging image of the material obtained in Example 2, c is the infrared thermal imaging image of the material obtained in Example 3, and d is the infrared thermal imaging image of the material obtained in Example 4; the excellent light-to-heat conversion performance of the material can also be further intuitively observed from the infrared thermal imaging images;
[0080] Photodynamic properties (ROS generation ability) test
[0081] Fig. 9 The fluorescence emission spectra of the nanomaterials prepared in Examples 1 to 4 of the present invention after being dispersed in aqueous solution and adding the active oxygen probe DCFH-DA; wherein a is the fluorescence emission spectra of Example 1 under NIRⅠ light (808nm, 1.0W / cm 2 ) after irradiation for 0 and 5 min, b is the fluorescence emission spectra of Example 2 under NIRⅠ light (808 nm, 1.0 W / cm 2 ) after irradiation for 0 and 5 min, c is the fluorescence emission spectra of Example 3 under NIRⅠ light (808 nm, 1.0 W / cm 2 ) after irradiation for 0 and 5 min, d is the fluorescence emission spectra of Example 4 under NIRⅠ light (808 nm, 1.0 W / cm 2 ) Fluorescence emission spectra after irradiation for 0 and 5 min; Fig. 9 As shown, with the extension of irradiation time, the fluorescence intensity of all examples gradually increased, but the increase range was different, which shows that the materials obtained in Examples 1 to 4 have the ability to generate ROS, especially Example 1 has the most outstanding ROS generation ability, and the peak value of the fluorescence intensity measured by its solution increased from 1251 to 70131 (56 times);
[0082] The antibacterial properties of the nanomaterials prepared in Example 1 of the present invention were tested:
[0083] The photothermal and photodynamic property test results of the material prepared in Example 1 showed that it had synergistic antibacterial effects of photothermal and photodynamic, and Escherichia coli and Staphylococcus aureus were selected to verify its antibacterial effect.
[0084] Fig.10 The nanomaterial prepared in Example 1 of the present invention is subjected to NIRⅠ light (808nm, 1.0W / cm 2 ) below the antibacterial comparison chart, take Escherichia coli (2×10 9 CFU / mL) was mixed with an aqueous solution of the material obtained in Example 1 with concentrations of 0 μg / mL, 100 μg / mL and 200 μg / mL, and the bacteria were cultured after irradiation with NIRⅠ light for 0, 10 and 20 min, and the growth of bacteria was observed with the naked eye after 24 hours; the results showed that when the bacterial solution without the obtained material was irradiated with laser, no obvious killing effect of the laser on the bacteria was observed within 20 min, while the laser irradiation with the prepared material showed obvious antibacterial effect on Escherichia coli, and the killing effect was concentration-dependent, and when the material concentration was 200 μg / mL, the bacteria could be completely killed within 20 min;
[0085] Fig.11The nanomaterial prepared in Example 1 of the present invention is subjected to NIR II light (1064nm, 1.0W / cm 2 ) after irradiation, Staphylococcus aureus (2×10 9 CFU / mL) was mixed with an aqueous solution of the material obtained in Example 1 at concentrations of 0 μg / mL, 100 μg / mL and 200 μg / mL, and the bacteria were cultured after irradiation with NIR II light for 0, 10 and 20 min, and the growth of the bacteria was observed after 24 h; Fig.10 Similar experimental conclusions, that is, the obtained material can effectively kill bacteria in a short time under laser irradiation. The above shows that the material prepared in the present invention is a potential new antibacterial material with excellent performance.
[0086] Fig.12 The schematic diagram of the preparation of the material of the present invention and its photothermal / photodynamic antibacterial properties is as follows: Fig.12 As shown, the material is prepared by mixing cobalt nitrate, 2-methylimidazole and dopamine hydrochloride. The prepared samples can exhibit excellent photothermal conversion performance under the irradiation of 808nm and 1064nm lasers and can generate ROS, thereby achieving the antibacterial purpose.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A one-step preparation method of a dopamine polymer having near-infrared II light absorption capability, characterized in that: include: dissolving cobalt salt and 2-methylimidazole in an organic solvent to obtain a mixed solution containing cobalt salt and 2-methylimidazole; Dopamine hydrochloride is added to the mixed solution containing the cobalt salt and 2-methylimidazole, and the mixture is reacted under preset conditions to obtain a dopamine polymer.
2. The one-step preparation method of the dopamine polymer having near infrared II region light absorption ability according to claim 1, characterized in that: The cobalt salt is cobalt nitrate.
3. The one-step preparation method of the dopamine polymer having near infrared II region light absorption ability according to claim 1, characterized in that: The molar ratio of the cobalt salt to 2-methylimidazole is 1:50-60, or 1:
55.
4. The one-step preparation method of the dopamine polymer having near infrared II region light absorption ability according to claim 1, characterized in that: The molar ratio of the cobalt salt to dopamine hydrochloride is 1:0.15 to 1:150, or 1:1.
5.
5. The one-step preparation method of the dopamine polymer having near infrared II region light absorption ability according to claim 1, characterized in that: The organic solvent is an ethanol aqueous solution.
6. The one-step preparation method of the dopamine polymer having near infrared II region light absorption ability according to claim 5, characterized in that: The volume ratio of the ethanol to water is 2:1 to 2:5, or 2:
3.
7. The one-step preparation method of the dopamine polymer having near infrared II region light absorption ability according to claim 1, characterized in that: The preset conditions are stirring at room temperature, hydrothermal reaction or ultrasonic reaction.
8. The one-step preparation method of the dopamine polymer having near infrared II light absorption ability according to claim 7, characterized in that: The stirring time at room temperature is 3 to 5 hours, or 4 hours; Or, the hydrothermal reaction is carried out at 110-130° C. for 2-6 h, or at 120° C. for 4 h; Alternatively, ultrasonic treatment is performed for 20 to 60 min, or 40 min.
9. Dopamine polymer having near infrared II region light absorption capability prepared by the method according to any one of claims 1 to 8.
10. Use of the dopamine polymer according to claim 9 in the preparation of photothermal / photodynamic antibacterial materials or devices.
Citation Information
Patent Citations
Application of poly-dopamine nano-particles
CN103908682A
Preparation method and application of hollow polydopamine nano material with high drug loading capacity
CN116874776A
Preparation method of polydopamine modified dimethylimidazole cobalt / molybdenum sulfide composite material
CN117583032A